Decision Analysis and Strategic Policy Formulation - Bunn, D. (Institutional Knowledge at Singapore Management University, 1977)
The role of decision analysis in the context of business policy is explored with the aid of a case study of a reorganization situation. This case study provides insights about the implementation of decision analysis in the policy field and also indicates guidelines for managers to follow in adapting the decision analysis approach to the resolution of the policy formulation problem.